Class politics in red and blue: explaining differences (and similarities) in what rich and poor want from government. (2nd January 2016) - Ellis, Christopher
Abstract : Much research suggests that the political views of wealthy people tend to be better represented in policy than those of the poor. But the degree to which this unequal representation is a normative problem for democracy remains the subject of some debate, simply because on many policy issues, the preferences of rich and poor are essentially indistinguishable from one another. Though rich and poor might have different material interests, in other words, they often share very similar views regarding what they want governments to do or not do. These high levels of policy agreement across class lines are puzzling, and beg the question of when and why self-interest matters to views on salient policy issues. This paper explores the contextual nature of income-based differences in public opinion, using contextual differences across US Congressional districts to understand why in some contexts rich and poor tend to want dramatically different things from government, while in other contexts they seem to be asking for many of the same things. The results show significant and systematic variation in the degree to which the policy views of rich and poor diverge from one another. By and large, rich and poor tend to be farthest apart in their views in Republican-leaning districts, as well as districts that are highly religious, rural, and located in the south. In general, then, the results suggest that political conflict between rich and poor is strongest in politically conservative contexts.